PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ADOBE FLASH CS 6 PADA PELAJARAN MATEMATIKA MATERI KPK DAN FPB - Muhamad Adib (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The purpose of this study is to develop innovative, practical and effective learning media in Mathematics with the material of the Biggest Fellowship Factor (FPB) and the Smallest Multiples Alliance (KPK). This research is motivated by the large number of MI who do not have adequate learning media. The development method in this learning media uses a rare method of research and development (Research and Development) developed by Sadiman consisting of 9 steps namely; 1) Analyzing needs, 2) Formulating objectives, 3) Formulating items, 4) Arranging gauges of success, 5) Writing media manuscripts, 6) Expert validation, 7) Trials, 8) Revisions, 9) Final manuscript products. The results of this study indicate that the Interactive Multimedia learning media based on Adobe Flash CS 6 falls into the feasible and effective category. This learning media is declared feasible based on the feasibility test according to media experts with a total percentage of 90.63% and valid material experts with a percentage of 91.46%. This learning media is effective based on effectiveness test with small group test results with a percentage of 90%, and large group trials with a percentage of 90.23%. Whereas in its application it was able to increase the grade average grade to 82.06. So that interactive multimedia learning media based on Adobe Flash CS 6 is included in the category of innovative, practical, effective and feasible to use.